Using fetal nuchal translucency to screen for major congenital cardiac defects at 10-14 weeks of gestation: population based cohort study - Hyett, Jon; Perdu, Marc; Sharland, Gurleen; Snijders, Rosalinde; Nicolaides, Kypros H (BMJ, 1999)
Abstract Objectives: To examine the utility of measuring fetal nuchal translucency thickness in screening for major defects of the heart and great arteries at 10-14 weeks of gestation. Design: Population based cohort study. Subjects: 29 154 singleton pregnancies with chromosomally normal fetuses at 10-14 weeks of gestation. Setting: Fetal medicine centre in London. Main outcome measure: Prevalence of major defects of the heart and great arteries. Results: Of 50 cases with major defects of the heart and great arteries (prevalence 1.7 per 1000 pregnancies) 28 (56%, 95% confidence interval 42% to 70%) were in the subgroup of 1822 pregnancies with fetal nuchal translucency thicknesses above the 95th centile of the normal range. The positive and negative predictive values for this cut off point of nuchal translucency thickness were 1.5% and 99.9% respectively. Conclusions: Measurement of fetal nuchal translucency thickness—traditionally used to identify fetuses at high risk of aneuploidy—at 10-14 weeks of gestation can identify a large proportion of fetuses with major defects of the heart and great arteries.